2009
DOI: 10.2105/ajph.2007.123927
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the Health Care System and the Use of Preventive Health Services by Older Black and White Adults

Abstract: Trust in one's own personal physician is associated with utilization of preventive health services. Blacks' relatively high distrust of their physicians likely contributes to health disparities by causing reduced utilization of preventive services. Health information disseminated to Blacks through informal means is likely to increase Blacks' utilization of preventive health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
285
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(297 citation statements)
references
References 39 publications
9
285
2
1
Order By: Relevance
“…The story of African Americans' mistrust of health care institutions and biomedical research has been told in many studies (e.g., Hall et al 2001;Musa et al 2009;Shoff and Yang 2012;White 2005). Their specific mistrust of human genetics research is only more recently becoming apparent (Bonham et al 2009;Bussey-Jones et al 2010;McDonald et al 2012;Skinner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The story of African Americans' mistrust of health care institutions and biomedical research has been told in many studies (e.g., Hall et al 2001;Musa et al 2009;Shoff and Yang 2012;White 2005). Their specific mistrust of human genetics research is only more recently becoming apparent (Bonham et al 2009;Bussey-Jones et al 2010;McDonald et al 2012;Skinner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although the credibility of health Web sites and pages may depend on site genres (Flanagin & Metzger, 2007;Iding, Crosby, Auernheimer, & Klemm, 2009), factors such as site design can counteract the effect of Web site genre on site credibility (Flanagin & Metzger). Meanwhile, a number of studies also measured consumers' global trust in various sources of health information, such as doctors, television, newspapers and magazines, relatives and friends, and the Internet (Khoo, Bolt, Babl, Jury, & Goldman, 2008;Musa, Schulz, Harris, Silverman, & Thomas, 2009;Narhi, 2007). This practice appears to be acceptable: Several Health Information National Trends Survey studies that use such measures have been published (Hesse et al, 2005;Hong, 2008;Ling, Klein, & Dang, 2006;McQueen, Vernon, Meissner, Klabunde, & Rakowski, 2006;Rains, 2007;Roach et al, 2009;44 Y. Ye Rutten, Augustson, Doran, Moser, & Hesse, 2009), and some of them have been highly cited McQueen et al;Ramanadhan & Viswanath, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent study has suggested that high levels of distrust in the health care system is associated with low odds of using preventive health services, controlling for other competing explanations. 49 Our results also imply that policies that target crime to help establish safe and cohesive neighborhoods may further reduce the impact of distrust on self-rated health. These macro-level actions can increase individuals' perception of health care performance and facilitate health.…”
Section: Discussionmentioning
confidence: 62%